Incidence of Sudden Cardiac Death in Low- and Middle-Income Countries: A Systematic Review of Cohort Studies. - Thakkar, Nandan; Alam, Prima; Thaker, Abhi; Ahukla, Aakansha; Shah, Jay; Saxena, Deepak; Shah, Komal (Indian Journal of Community Medicine)
Sudden cardiac death (SCD) is a leading cause of mortality worldwide and, in recent years, has become an urgent public health concern in low- and middle-income countries (LMICs). Data from LMICs, however, remains limited. As such, the aim of this article is to systematically review the current literature on the incidence of SCD in LMICs to inform policymakers and identify potential research gaps. A search of PubMed and Embase was utilized to capture the targeted condition, outcome, and setting. Only peer-reviewed cohort studies in LMICs reporting SCD incidence estimates in the general population of individuals aged ≥1 year were eligible for selection. Papers providing incidence data for specific types of SCD, including sudden coronary death or death from sudden cardiac arrest, were also included. After deduplication, 1941 citations were identified and screened. Seven studies representing four countries--Cameroon, China, India, and Iran--met the criteria for inclusion and were considered in our analysis. The crude incidence rate for SCD ranged from 19.9 to 190 cases per 100,000 person-years, while ageadjusted rates ranged from 33.6 to 230 cases per 100,000 person-years. There was notable variability in methods utilized to ascertain SCD cases. These findings suggest that the incidence of all-cause SCD in LMICs and may exceed that of high-income countries; however, observed disparities may be partly attributable to differences in case ascertainment methods. Additional research is needed to better understand the true incidence of SCD in developing countries. It is crucial that future studies across regions utilize standard diagnostic criteria and methodology for identifying SCD, which would provide a framework by which to compare outcomes between settings.